1985
DOI: 10.1071/sr9850131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different organic wastes upon water retention, transmission and contact characteristics of a sandy soil

Abstract: Small cylinders were filled to a depth of 20 cm with Ludas sand to which different organic wastes, viz. sewage sludge, press mud, green manure and farmyard manure had been added up to a maximal rate equivalent to 827, 1043, 1370 and 542 t/ha. The cylinders were set in the ground and kept moist. At the end of 308 days' equilibration period, the samples were used for measuring soil water retention, saturated hydraulic conductivity as well as the horizontal infiltration with 0.01 M CaCl2 and alcohol. An apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
10

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 12 publications
3
16
0
10
Order By: Relevance
“…Mulching techniques have emerged in recent years to address these soil constraints yielding positive results in a variety of scenarios. An early study by Kumar et al (1985) and other more recent studies (Kar & Kumar, 2007;Mubarak et al, 2009;Okonkwo et al, 2011;García-Moreno, 2013;López et al, 2014;Zribi et al, 2015) reported the positive effects of mulches and organic amendments on soil physical properties, such as increased water retention and decreased soil evaporation.…”
Section: Measurementsmentioning
confidence: 95%
“…Mulching techniques have emerged in recent years to address these soil constraints yielding positive results in a variety of scenarios. An early study by Kumar et al (1985) and other more recent studies (Kar & Kumar, 2007;Mubarak et al, 2009;Okonkwo et al, 2011;García-Moreno, 2013;López et al, 2014;Zribi et al, 2015) reported the positive effects of mulches and organic amendments on soil physical properties, such as increased water retention and decreased soil evaporation.…”
Section: Measurementsmentioning
confidence: 95%
“…Entretanto, dada a presença de metais pesados neste material, deve-se evitar a utilização de doses excessivas, as quais são calculadas de acordo com teor inicial de metais pesados no solo; quantidade total adicionada de metais pesados; carga total cumulativa de elementos metálicos; toxidez desses elementos para as plantas; valores limites de concentração de metais pesados nos solos; interação entre os elementos e características dos solos; e sensibilidade da planta (Kabata-Pendias & Pendias, 1992). Na literatura, encontram-se vários trabalhos que evidenciam o efeito benéfico da matéria orgânica na estabilidade de agregados (Wei et al, 1985;Jorge et al, 1991;Hadas et al 1994;Campos et al, 1995;Albiach, 1997;Martinez-Mena et al, 1998;Beutler et al, 2001;Grandy et al, 2002;Whalen & Chang, 2002) e na resistência do solo à penetração (Kumar et al, 1985;Smith et al, 1997). A aplicação de biossólido, além de aumentar o teor de matéria orgânica, pode aumentar a agregação e alterar a proporção de agregados estáveis em água (Jorge et al, 1991).…”
Section: Introductionunclassified
“…Em relação aos atributos físicos, a aplicação de lodo de esgoto promove aumento na porosidade total e macroporosidade (Ortega et al, 1981;Pagliai et al, 1981;Mathan, 1994), diminuição na densidade do solo (Aggelides & Londra, 2000) e maior retenção de água (Kumar et al, 1985;Aggelides & Londra, 2000;Debosz et al, 2002). Jorge et al (1991), estudando a adição de 10,0 Mg ha -1 ano -1 de lodo de esgoto em Latossolo Vermelho argiloso, não verificaram alterações na retenção de água nas tensões de 0,03 e 0,1 MPa, mas verificaram alterações na relação macro e microporos sem, no entanto, alterações significativas na porosidade total e densidade do solo.…”
Section: Introductionunclassified